On Dallas Smythe’s “Audience Commodity”: An Interview with Lee McGuigan and Vincent Manzerolle - Henry Adam Svec (tripleC: Communication, Capitalism & Critique)
This interview with Lee McGuigan and Vincent Manzerolle explores some concepts and debates charted by their new co-edited book, The Audience Commodity in a Digital Age: Revisiting a Critical Theory of Commercial Media, which both celebrates and scrutinizes Dallas Smythe’s canonical 1977 essay, “Communications: Blindspot of Western Marxism”. The discussion covers Smythe’s contribution to the field of media studies and the state of current debates pertaining to the theory of the audience commodity, and it also touches on questions of Smythe’s mainstream reception and legacy.